Open innovation for sustainability: opportunities and challenges for Japanese companies - Kitaura, Akari (2024)
The sustainability issues we face today are very complex that no individual organization can solve them alone. Open innovation emerged as a potent strategy to address such societal challenges while also creating economic value, framework known as creating shared value (CSV). However, current literature lacks practical studies on factors that motivate and challenge the adoption of open innovation, as well as their connection between open innovation and CSV. The aim of this research is to uncover opportunities and challenges Japanese companies identify in open innovation, and how this approach leads to creating shared value. 16 semi-structured interviews with open innovation facilitators and Japanese firms were conducted to gain insights into how open innovation is perceived in Japanese business. A thematic analysis was conducted for this study. The findings revealed three major opportunities Japanese companies identify in open innovation: 1) infusion of new blood into the organization 2) acceleration of innovation process 3) attainment of trust and pride. Four common challenges were also identified: 1) lack of understanding by the person in charge 2) fear of failure 3) different speed among the involved parties 4) varying levels of awareness and enthusiasm towards sustainability challenges. The study indicates that these challenges are largely attributed to Japanese unique corporate culture. Identifying the areas for improvement would facilitate the adoption of open innovation in Japanese firms. Furthermore, the findings show that open innovation generates shared value by creating collaborative ecosystems, optimizing resource utilization, and enabling larger firms to tap into startups’ fast innovation lifecycle. On the other hand, high prices for sustainable products are a major obstacle to creating shared value through open innovation. Therefore, the consideration of affordability would help to maximize the potential for businesses to create shared value.